INTEGRASI NILAI ISLAM DALAM BUDAYA NAGARI: STUDI KOMPARATIF PERILAKU KEAGAMAAN MASYARAKAT DI KOTO BARU, AMPANG KURANJI, DAN TIUMANG (KABUPATEN DHARMASRAYA) - Nur Ja'a, Ainun; Martineli, Yelly; Ucelorenza; Anggala Perdana, Roland; Haryani, Dita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research examines the degree to which Islamic teachings have been absorbed into nagari cultural practices and how this absorption shapes the religious character of communities across three nagari in Dharmasraya Regency: Koto Baru, Ampang Kuranji, and Tiumang. The study departs from the distinctive reality that Islamic law and Minangkabau customary traditions have long coexisted harmoniously under the philosophical framework of Adat Basandi Syarak, Syarak Basandi Kitabullah (ABS-SBK). A comparative qualitative methodology was employed, drawing on participatory fieldwork, in-depth interviews, and documentary review. Findings reveal that ABS-SBK is enacted through communal practices such as Yasinan recitation, Slametan gatherings, and periodic religious study circles, each functioning both as a conduit for religious instruction and a mechanism for social cohesion. Despite their geographical proximity, the three nagari exhibit discernible differences in how local culture is practiced, attributable to demographic composition, historical patterns of population movement, and the density of social exchange among residents. The study concludes that Islamic value integration unfolds through an acculturation dynamic that reinforces religious identity while preserving ancestral customs, producing a distinctive socio-religious equilibrium across Dharmasraya Regency.